PENGARUH PERMAINAN LAMPU LAVA TERHADAP KETERAMPILAN SAINS ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 1 KECAMATAN SAIL PEKANBARU - Yolanda Kaisar; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the results of field observations on the science of children's skills have not developed optimally so it needs to be done the application of lava lamps. This study aims to determine the influence of the game of lava lamps on the science skills of children aged 5-6 years in TK Negeri Pembina 1 Sail Pekanbaru District. The sample used in this study was 15 students. The data collection technique used is observation. Technique of data analysis using t-test test by using program of SPSS 20. The research hypothesis is activity of game of lava lamp have influence to science skill of children aged 5-6 years in TK Negeri Pembina 1 Kec Sail Pekanbaru. This can be known from the analysis of data obtained t count = 26,750 and Sig. (2-tailed) = 0.000. Because Sig. (2-tailed) = 0.000 <0,05 it can be concluded that there is a significant difference in students' science skills after the use of lava lamp play in the learning process. So it means Ho is rejected and Ha accepted which means there is a very significant difference between before and after doing experiment by applying lava lamp game. The influence of the game of lava lamp on the science skill of children aged 5-6 years in TK Negeri Pembina 1 Kecamatan Sail Pekanbaru amounted to 64.70%.Keywords: Science Skill, Lava Lamp Game